Pendampingan Mahasiswa KPM Insuri Ponorogo Melalui Bimbel (Non Formal) untuk Meningkatkan Motivasi Belajar Anak di Dukuh Mirah, Desa Nambangrejo, Kecamatan Sukorejo, Kabupaten Ponorogo: Bimbel - Khasanah, Uswatun; Nafiah, Tsalits Maratun (Social Science Academic, 2025)
Tutoring is additional learning for students outside of school. Tutoring plays a very important role in children's learning development, because not only what is learned at school, but learning outside of school has quite a big impact and influences students' learning motivation. Non-formal education is expected to increase students' interest or interest in learning. In non-formal education, students are invited to learn using different methods to formal education in general, non-formal education is more relaxed and interesting by introducing something new or interesting that they don't yet understand, in contrast to formal education, learning is more fun by playing. games as a distraction and also as an addition to learning. Students are not only required to be able to memorize but also have to understand and be interested, because by being interested students will automatically know what they don't know. For this reason, learning and playing methods are applied in order to motivate students to learn to become more creative individuals and also active in thinking and solving problems.